Strategi Pengembangan Usaha Mikro, Kecil dan Menengah (UMKM) di Kota Pematangsiantar - Robert Tua Siregar; Hery Pandapotan Silitonga; Juan Anastasia Putri (Universitas Medan Area, 2020)
The purpose of this study was to determine the development strategy of Micro, Small and Medium Enterprises (UMKM) in Pematangsiantar City. The research model is a qualitative approach. The research design is field study and literature study. The focus of research to be achieved is the development strategy of Small, Micro and Medium Enterprises in Pematangsiantar City. The data analysis technique used is descriptive qualitative analysis. The results of the study show that UMKM entrepreneurs face obstacles in developing their businesses. The strategy of developing MSMEs in Pematangsiantar City is inseparable from the participation of the government and UMKM actors. The government should be able to provide assistance to UMKM actors, as well as socialization and training, and UMKM actors should be more creative and innovative in producing goods